Levels of uranium and thorium in maternal scalp hair and risk of orofacial clefts in offspring. (August 2019) - Wei, Yihui; Jin, Lei; Li, Zhiwen; Liu, Jufen; Wang, Linlin; Pi, Xin; Yin, Shengju; Wang, Chengrong; Ren, Aiguo
Abstract: Uranium and thorium are common radioactive elements that exist in the environment. However, few environmental epidemiological studies have focused on their possible effects on congenital malformations. Here, we explored the association between uranium and thorium concentrations in maternal scalp hair grown from 3 months before to 3 months after conception, namely during the periconceptional period and the risk of orofacial clefts (OFCs) in offspring. Our study included 153 women whose pregnancies were affected by OFCs (cases) and 601 women who delivered infants without birth defects (controls) from four provinces in China. Face-to-face interviews were used to collect sociodemographic characteristics with a structured questionnaire. Concentrations of uranium and thorium in maternal scalp hair grown during the periconceptional period were detected using inductively coupled plasma-mass spectrometry. The risk of OFCs in association with higher concentrations of the two radioactive elements was estimated using odds ratios (ORs) and 95% confidence intervals (CIs) while adjusting for potential confounding factors. The levels of uranium and thorium in maternal hair were in agreement with the published literature. After adjusting for several confounders, the ORs of thorium in the highest, upper, and lower quartile versus the lowest quartile were 2.63 (95% CI, 1.41–4.92), 1.98 (95% CI, 1.03–3.79), and 2.73 (95% CI, 1.46–5.12), respectively. No association was found between levels of uranium and the risk of OFCs. Maternal periconceptional exposure to thorium may be a risk factor for OFCs in offspring. Highlights: Orofacial clefts are among the most common congenital anomalies whose etiology is not fully understood. Association between levels of uranium and thorium in maternal hair and risk for orofacial clefts in offspring was examined. Uranium and thorium concentrations in maternal scalp hair were taken as the biomarkers of exposure. A higher level of thorium in maternal hair was associated with an increased risk for orofacial clefts in offspring. No association was found between levels of uranium in maternal hair and the risk for orofacial clefts in offspring.